Влияние механизмов сегрегации на смещение границ раздела и стабильность сверхтвердых нанокомпозитов Zr-Ti-Si-N - Погребняк, А.Д.; Соболь, О.В.; Береснев, В.М.; Турбин, П.В.; Толмачева, Г.Н.; Махмудов, Н.А.; Шипиленко, А.П.; Каверин, М.В.; Пшик, А.В.; Фурсова, Е.В. (Харківський національний університет імені В.Н. Каразіна, Науковий фізико-технологічний центр МОН та НАН України, 2009)
Впервые с помощью вакуумно-дугового осаждения в ВЧ разряде были получены сверхтвердые наноструктурные покрытия с Н (твердостью) ≥55,3 ГПа. Проведен анализ влияния высокотемпературного отжига в вакууме 1180 С и воздушной среде 800 С на фазовый состав, структуру и напряженное состояние ионно-плазменных покрытий Zr-Ti-Si-N. Высокотемпературный отжиг при температуре ≥1180 С приводит к усилению сегрегационных процессов, протекающих по спинодальному механизму на границах нанозерен. В результате формируется модулированная структура с периодически изменяющейся концентрацией объемных фаз nc-ZrN; nc-(Zr, Ti)N и -Si3N4. Рассмотрено два режима осаждения покрытий. Определяющим субструктурные характеристики нанокристаллитов (Zr, Ti)N твердого раствора в температурном интервале 25 1180 С является процесс увеличения размера зерна от 12 до 25 нм, при незначительном понижении микродеформации решетки. Вперше за допомогою вакуумно-дугового осадження у ВЧ розряді були отримані надтверді наноструктурні покриття з Н (твердістю) ≥55,3 ГПа. Проведений аналіз впливу високотемпературного відпалювання у вакуумі 1180 С і повітряному середовищі 800 С на фазовий склад, структуру і напружений стан іонно-плазмових покриттів Zr-Ti-Si-N. Високотемпературне відпалювання при температурі ≥1180 С призводить до посилення процесів сегрегації, що протікають за спінодальним механізмом на межах нанозерен. У результаті формується модульована структура з концентрацією об’ємних фаз nc-ZrN, що періодично змінюється; nc-(Zr, Ti)N і -Si3N4. Розглянуто два режими осадження покриттів. Визначальним для субструктурних характеристик нанокристалітів (Zr, Ti)N твердого розчину в температурному інтервалі 25 1180 С є процес збільшення розміру зерна від 12 до 25 нм, при незначному зниженні мікродеформації гратки. The paper reports results of studies concerning structure, phase composition, and physical-mechanical properties of nanocomposite superhard coatings ZrN and Zr-Ti-Si-N with varying Ti and Si concentrations. The coatings were fabricated using vacuum-arc method, according to a standard scheme, under direct current, and with HF (High Frequency Discharge). Zr target sputtering in nitrogen atmosphere resulted in formation of zirconium nitride coatings. Zr-Ti-Si-N coating had high thermal stability of phase composition and remained structure state under thermal annealing temperatures reached 1180 С in vacuum and 800 С in air. Effect of isochronous annealing on phase composition, structure, and stress state of Zr-Ti-Si-N ion-plasma deposited coatings (nanocomposite coatings) was reported. Vacuum annealing increased sizes of solid solution nanocrystallites from (12 to 15) in as-deposited coatings to 25 nm after annealing temperature reached 1180 С. One could also find macro- and microrelaxations, which were accompanied by formation of deformation defects, which values reached 15,5 vol.%. Under 530 С annealing in vacuum or in air, nanocomposite coating hardness increased, demonstrating, however, high spread in values from 29 to 54 GPa (first series of samples). When Ti and Si concentration increased (second series) and three phases nc-ZrN, (Zr, Ti)N-nc, and -Si3N4 were formed, average hardness increased to 40,8 ± 4 GPa, (second series of samples). Annealing to 500 С increased hardness and demonstrated lower spread in values H = 48 ± 6 GPa and E = (456 ± 78) GPa.
Keywords: сверхтвердые нанокомпозиты; напряжение сжатия; спинодальная фаза сегрегации